2009
DOI: 10.1111/j.1751-1097.2008.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Crayfish Procambarus clarkii Retina and Nervous System Exhibit Antioxidant Circadian Rhythms Coupled with Metabolic and Luminous Daily Cycles

Abstract: Based on previous work in which we proposed midgut as a putative peripheral oscillator responsible for circadian reduced glutathione (GSH) crayfish status, herein we investigated the retina and optic lobe-brain (OL-B) circadian GSH system and its ability to deal with reactive oxygen species (ROS) produced as a consequence of metabolic rhythms and light variations. We characterized daily and antioxidant circadian variations of the different parameters of the glutathione system, including GSH, oxidized glutathio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
(43 reference statements)
8
19
0
Order By: Relevance
“…Since then, GSH circadian oscillation has been confirmed in many studies across several different species, including rat, mouse, crayfish, and human (6,11,51,82). Further studies have shown that GSSG also shows daily patterns of expression, as well as the enzymes GPx, GR, and GST (1,6,11,37,42,100,109).…”
Section: Rhythmicity Of the Cellular Antioxidant System: Patterns Of mentioning
confidence: 83%
See 1 more Smart Citation
“…Since then, GSH circadian oscillation has been confirmed in many studies across several different species, including rat, mouse, crayfish, and human (6,11,51,82). Further studies have shown that GSSG also shows daily patterns of expression, as well as the enzymes GPx, GR, and GST (1,6,11,37,42,100,109).…”
Section: Rhythmicity Of the Cellular Antioxidant System: Patterns Of mentioning
confidence: 83%
“…Several studies have shown evidence of differences in DNA damage, lipid peroxidation, and protein oxidation at different times of the day, thus indicating circadian oscillations of oxidative stress responses (51,90,97,100,176). These oscillations relate directly to the daily rhythm of antioxidant expression and protective enzyme activity levels (Fig.…”
Section: Rhythmicity Of the Cellular Antioxidant System: Patterns Of mentioning
confidence: 95%
“…However, in the two species P. clarkii and Procambarus digueti, the antioxidant systems are known to be very robust in their diel changes (270) and entrain to light phases (271). Especially the glutathione-system in the eyestalk and the brain of P. clarkii exhibits clear-cut circadian rhythmicity (272,273).…”
Section: Melatoninmentioning
confidence: 99%
“…In crustaceans, the synthesis of GSH occurs in the hepatopancreas and the gills, and synthesis of GSH is better with higher luminous intensity (Maciel et al 2004). With the growing number of redox reactions, the metabolism and production of reactive oxygen species (ROS) decrease glutathione levels (Fanjul-Moles et al 2009). The second reason is a steadily decreasing amount of polyunsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…The second reason is a steadily decreasing amount of polyunsaturated fatty acids. According to Fanjul-Moles et al (2009), the Procambarus clarkii membrane is very rich in phospholipids and PUFAs, and even low exposition to light as well as the lowest possibility of production of ROS induce a decrease in important components of the membrane and open up access into the organism (Balzer et al 1997). …”
Section: Introductionmentioning
confidence: 99%